The Philosophy of Education and Knowledge in the view of Ghazali (Raparin Journal of Humanities (RJH), 2024)
The abstract of this paper includes sources and methods of access to knowledge and methodic doubt in Ghazali viewpoint and describing the concept of education in the philosophy of Ghazali. The sources of obtaining knowledge in al-Ghazali’s view are not only the senses and the intellect, but also the revelation of the prophets. This means that the prophets own a special knowledge that is not normal to all the people, and the ordinary people must follow. The senses communicate the knowledge of mind, but reaching the truth is not achieved through feelings and minds alone. Emotions and thoughts are doubtful and often deceive us. We do not reach the knowledge of certainty, especially in metaphysical matters. The things that fall on the other side of the world are feelings, so Ghazali uses doubt to reach the knowledge of certainty, and this can be found through guessing. Ghazali thought that human could achieve the truth through the incident. The term ‘Education’ is used in every language which all focus on the preparation and training. Islam has given great importance to education and the Holy Qur'an itself. Imam Ghazali has played a major role in Islamic education. He has many writings, such as ‘Ihya Uloom al-Din’, which is a valuable encyclopedia of renewing the Islamic sciences and Islamic education. Ghazali tried to turn Islamic education towards Sufism. And the goal of Islamic education is to prepare a single believer committed to achieving happiness.